Health policy, health systems research and analysis capacity assessment of the school of public health, University of Ghana - Agyepong, I.A.; Anniah, K.; Aikins, M.; Akweongo, P.; Esena, R.; Mirzoev, T. (Ghana Medical Journal, 2015)
Introduction: Health Policy and Systems Research and Analysis (HPSR&A) is an applied science that deals with complexity as it tries to provide lessons, tools and methods to understand and improve health systems and health policy. It is defined by the kinds of questions asked rather than a particular methodology. Objective: Our objective was to assess capacity and capacity strengthening needs for HPSR&A conduct and teaching in the University of Ghana School of Public Health (UG-SPH). We conceptualized dynamically inter-related levels of capacity as contextual, institutional and individual. Methods: The study had a cross sectional, mixed methods design. Data collection involved desk review, ,an in-depth interview, focus group discussions (FGD) and an interviewer administered questionnaire with closed and open ended items. Netmap was used as a tool in the FGD. Findings: At all levels, HPSR&A capacity exists in Ghana but is somewhat fragile. The fragility reflects in part contextual challenges related to national income and priorities as well as the fact that globally HPSR&A remains an emerging field. At the contextual level, Institutions involved in some way or other in HPSR&A were part of larger organizations with broader mandates. Only a handful of SPH staff indicated that they specifically do teaching and /or research related to HPSR&A. Conclusion & Recommendations: There is a need to raise awareness of the field of HPSR&A and its potential contributions to health sector development; build upon already existing contextual, institutional and individual capacity; and also attract and develop the next generation of researchers and teachers.
Keywords: Health Policy; Health Systems; Research; Teaching; Capacity